A multiplexed gene expression study on nasopharyngeal carcinoma treated with xiao xian xiong decoction - Leu, Kim Fey (2023)
Nasopharyngeal carcinoma (NPC) is a rare head and neck malignancy in the Western countries, but relatively common in Southern Asia. So far, the most common clinical means of treatment are generally radiotherapy (RT), with or without concurrent chemotherapy (CT). The use of traditional Chinese medicine (TCM) as a complementary and adjuvant medicine for the treatment of NPC is getting more attention as to reduce the side effects caused by radiotherapy and chemotherapy. Traditional Chinese herbal prescription Xiao Xian Xiong Decoction (XXXD), is made up of 3 Chinese herbal medicines, namely Huanglian (Coptis chinensis Franch. C. deltoidea, or C. teeta Wall), Banxia (Pinellia ternate (Thunb.)Breit.), Gualuo (Trichosanthes kirilowaii Maxim. or Trichosanthes rosthornii Harms). This project was designed to study the cytotoxic effect and global gene expression induced by XXXD on a selected NPC cell lines as well as to reveal the phytochemicals found in these Chinese herbal medicines. A Nanostring platform named nCounter XT Gene Expression Assay was carried out on extracted RNA and to further study on the gene expression in 13 canonical pathways, the cytotoxic effects of the individual herb and in combination of two and three herbs were studied on 8 nasopharyngeal cancer cell lines, namely TWO-1, TWO-4, HONE-1, SUNE1, CNE-2, HK-1, CNE-1 and C666-1. Out of the 7 groups of herbal extract samples, Huanglian showed the highest cytotoxicity against 8 NPC cell lines with the lowest IC50 of 4.48 µg/mL recorded for HONE-1. The IC50 values obtained for XXXD treated HONE-1 and CNE-2 cell lines were 88.55 and 92.95 µg/mL respectively. The Nanostring gene expression result showed that of HONE-1 upon treatment with L1(Huanglian) at 4 hours, 8 hours and 12 hours vs. 0 hour, initiated downregulation of THBS1, IL7R, CCND1, FN1, BCL2L and VEGEFC genes in PI3K, MAPK and RAS pathways which conventionally associated with functions of promoting cell proliferation and growth. The cytotoxicity of Huanglian towards HONE-1 could further be ascertained. Besides, gene expression of HONE-1 upon treatment with L7 (XXXD) at 4 hours, 8 hours and 12 hours vs. 0 hour showed that HONE-1 was imposed to apoptosis. The amplified expression of CDKNIA, CDKNIC and TNFSF10 initiated in Cell Cycle pathway apparently inhibited cell cycle progression in HONE-1. Moreover, enhanced expression in SOCS3 and ID2 together with downregulation of anti-apoptotic genes BCL-2 and BCL-XL initiated in JAK-STAT pathway further exacerbated cell fate of HONE-1.This study suggests that XXXD could be envisaged as a potent anticancer traditional Chinese herb targeting HONE1 cancer cell line.